Opportunities Of Education to Increase the Financial Literacy of The Young Generation on The Way of Introduction and Development of New Banking Services in Commercial Banks (Zien Journal of Social Sciences and Humanities, 2022)
In this scientific article, the introduction of new types of banking services in the commercial banks of the country, first of all, studies the demand of the population for new types of banking services and requires them to use new innovative services to improve their skills. and literacy. Therefore, first of all, it is necessary to launch the knowledge and skills of the younger generation by improving the financial literacy of young people graduating from general education schools, lyceums and colleges Today, the methodological approaches of international financial institutions and the theoretical views of scientists are aimed at improving the financial literacy of young people, as it requires the financial literacy of the population from an early age to improve their knowledge, skills and abilities. The results of a study conducted by the World Bank and the Organization for Economic Cooperation and Development (OECD) on improving the financial literacy of the population in different countries are summarized. In addition, this scientific article presents scientific proposals and practical recommendations for the formation of financial literacy and the creation of mechanisms for its implementation and increase its effectiveness for the younger generation in our country.